THE INFLUENCE OF SERVICE QUALITY AND THE APPLICATION OF ISLAMIC VALUES ON CUSTOMER SATISFACTION IN ISLAMIC BANK, A STUDY OF CUSTOMERS IN SUKMAJAYA SUB-DISTRICT - Pratama, Rakha; Sardiana, Anna (Ibs Press, 2025)
This study aims to determine the relationship and the magnitude of the influence on service quality and the application of Islamic values on customer satisfaction at Islamic banks in Sukmajaya District. The method used in this research is quantitative method by distributing questionnaires and using multiple linear regression analysis techniques. The population in this study were Islamic bank customers with a research sample of 150 respondents spread across Sukmajaya district area. The results in this study indicate that both variables have a positive influence on customer satisfaction in Islamic banks, both partially tested and simultaneously tested. The two independent variables in this study, which is the variables of service and the application of Islamic values both have a strong influence on customer satisfaction in Islamic banks. Therefore, the results of this study are expected to be a consideration for the management of Islamic banks in Sukamjaya District in making decisions related to increasing the number of customers and are expected to be used as reference material for previous research.